An Integrated Fuzzy Model for Resilient Supplier Selection - Moslem Alimohammadlou; Abbas Bonyani (International Journal of Supply Chain Management, 2018)
Nowadays, the business environment has provided causes of emerging a high level of uncertainty and turbulent behavior in supply chains. In most cases, suppliers are considered as the main sources of external risks which provide causes of emerging wide levels of disruptions in supply chains; therefore, choosing the appropriate and also resilient suppliers can greatly reduce purchasing costs and delay times and also increase the ability to maintain business in the case of disruption, competitiveness of the company and satisfaction of customers. This study is aimed to identify and investigate the attributes for evaluating the suppliers resilience from the two aspects, the importance and effectiveness of choosing the resilient suppliers in Iran electronic industries. In this regard, screening, dematel, analytic network process and goal programming have been used that they were performed in the fuzzy environment due to the uncertainty of the nature of all researches. Results showed that some attributes including, human resource management, visibility, and financial strength are the most influential factors. In terms of importance, agility, adaptability, and vulnerability are also the most important factors. At the end, while presenting a case study of the industry and applying goal programming, the ability of the proposed combined model in solving the real-world problems is shown.